1963
DOI: 10.1104/pp.38.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Floral Induction by Inhibitors of Steroid Biosynthesis

Abstract: This paper concerns a class of metabolic inhibitors which possess the ability to suppress the flowering of short-day plants and which appear to do so by interfering with generation of the flowering stimulus by the leaf. The inhibition of flowering with which we are here concerned is thus different from that elicited by 5-fluorouracil and 5-fluorodeoxyuridine. These two substances act by preventing successful receipt by the bud of the leaf-produced floral stimulus (4,17). The substances here reported as active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

1964
1964
1985
1985

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…Four-day-old Pharbitis seedlings grown in the standard vermiculite-granite mixture respond to exposure to one 16-hour dark period at 27°by the subsequent initiation of 6 to 7 flower buds, including a terminal one (1,14). The axillary buds of the lowest 2 nodes of such seedlings remain vegetative, but the buds on the third and all higher nodes are transformed into flower buds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four-day-old Pharbitis seedlings grown in the standard vermiculite-granite mixture respond to exposure to one 16-hour dark period at 27°by the subsequent initiation of 6 to 7 flower buds, including a terminal one (1,14). The axillary buds of the lowest 2 nodes of such seedlings remain vegetative, but the buds on the third and all higher nodes are transformed into flower buds.…”
Section: Methodsmentioning
confidence: 99%
“…1 Received Aug. 30,1963. 2 Supported by grants from the Herman Frasch Foundation for Agricultural Chemistry, and from the National Science Foundation (G-17483).…”
Section: Methodsmentioning
confidence: 99%
“…Applying SK&F 7997-A3 to the illuminated cotyledon at the time of starting induction had no effect on flowering. The short lived nature of the sensitivity of flowering on applying this compound (2) implies that it may be unstable in the plant. When we applied SK&F 7997-A3 to the illuminated cotyledon 8 h after the start of the dark period promotion of flowering and inhibition of photosynthesis was found (Table IV).…”
Section: Methodsmentioning
confidence: 99%
“…6), the only data which argue, compellingly, for leaf localization of effects on flowering are for applications of SK&F 7997-A3,2 ethylene, cycloheximide, and kinetin (21). All three criteria necessary for validating leaf-localized action have been met only for studies of suppression of flowering by SK&F 7997-A3 (2) and by ethylene (17). The question of possible transport to the apex has not been examined adequately for responses either to cycloheximide (15) or kinetin (13).…”
mentioning
confidence: 99%
“…'I'he third method of dual treatmilenit yielded evidleilce that S:K&F 7997-.\ interacts noncompetitivelv vitih GA. in the re-gulation of shoot elongation. }11onoer et al ( 2) reported that a iiinimber of coinl)ounins klioo-i as inhiibitors of steroi(l biosynthesis w ere effective in supl)pressing floral iiidictioni in 2 short-day pilants, Xanitliiiuni pio oIslvaiiicomui anld Pharbitis nil. Among the coipouiids founid to be most effective as floweriiig iiliibitors w-as Tris-(2-diethli--aminioethyl) -phosphate trihydrochloride (SK&F 7997-.\) .…”
mentioning
confidence: 99%